Modeling the Factors Influencing the Adoption of a Map-Based Disaster Application in Indonesia: A Case of SIKK Magelang - Sari, Kartika Puspita; Kanegae, Hidehiko (TDMRC, Universitas Syiah Kuala, 2020)
Indonesia has high exposure to natural hazards, frequent disaster events, and a highly vulnerable population. Hence, risk communication and disaster information dissemination are crucial to reducing risks. Numerous disaster mobile applications (apps) with location-based services or maps already exist for facilitating risk communication to the public; however, availability does not automatically translate into use or adoption. Therefore, to understand the factors influencing the adoption of a map-based disaster app, the factors that affect the adoption of a local government-initiated map-based disaster app in Indonesia, namely Sistem Informasi Kebencanaan Kabupaten Magelang, or Disaster Information System of Magelang Regency (SIKK Magelang), were examined through the theoretical lenses of a combined information system (IS) success model. Partial Least Squared Structural Equation Modelling (PLS-SEM), with the help of Smart-PLS, was used to examine the hypothesized relationships among the proposed constructs (latent variables). Nine exogenous latent variables were proposed as the antecedents of intention to use a map-based disaster application (the endogenous latent variable), including information quality, system quality, familiarity with online maps, perceived usefulness, user satisfaction, facilitating conditions, risk perceptions, information seeking behavior, and perceived quality of the Internet connection. Information-seeking behavior was also predicted to be influenced by risk perception. A questionnaire survey with an app trial was conducted in Magelang Regency for data collection. The study results confirmed the applicability of the combined IS success model frameworks in predicting the adoption of this map-based disaster app by the public. Although new constructs representing disaster-related online maps and familiarity with those maps were initially proposed in the contextual model, the model validation results showed that intention to use SIKK Magelang was significantly influenced only by perceived usefulness and user satisfaction. Practically, this studys results offer guidance to the local emergency managers in Indonesia, especially Magelang Regency, regarding how to develop strategies to increase the apps adoption.